2017
DOI: 10.1177/0284185117733297
|View full text |Cite
|
Sign up to set email alerts
|

In vivo MR spectroscopy predicts high tumor grade in endometrial cancer

Abstract: Background In vivo magnetic resonance spectroscopy (MRS) enables non-invasive measurements of tumor metabolites. Choline-containing metabolites play a key role in tumor metabolism. Purpose To explore whether preoperative MRS-derived tumor choline levels are associated with clinical and histological features in endometrial carcinomas. Material and Methods Preoperative pelvic magnetic resonance imaging (MRI) (1.5T), including structural and diffusion-weighted imaging and localized multivoxel proton MR (1H-MR) sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
3
2
2
Order By: Relevance
“…The Cho/water for EC patients with deep myometrial invasion, as well as with lymph node metastasis, was significantly higher than that with superficial myometrial invasion, as well as without lymph node metastasis. This is different from previous study [ 17 ], which has shown that the differences are not statistically significant. There was no significant difference in the Cho/water between patients with and without cervical invasion, which was in line with the previous study [ 17 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The Cho/water for EC patients with deep myometrial invasion, as well as with lymph node metastasis, was significantly higher than that with superficial myometrial invasion, as well as without lymph node metastasis. This is different from previous study [ 17 ], which has shown that the differences are not statistically significant. There was no significant difference in the Cho/water between patients with and without cervical invasion, which was in line with the previous study [ 17 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This is different from previous study [ 17 ], which has shown that the differences are not statistically significant. There was no significant difference in the Cho/water between patients with and without cervical invasion, which was in line with the previous study [ 17 ]. The heterogeneity of MRS Cho/water within solid part of EC was studied in our previous study [ 6 ], which showed that the Cho/water heterogeneity of Ib and III EC was significantly greater than that of Ia EC; and the Cho/water heterogeneity of EC was increased with the increased tumor stage and size.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In some cancer cell types, such as isolated breast and ovarian cancer cells, a relative decrease of GPCho was observed as well, which led to the suggestion to use a higher ratio of PCho/GPCho as a marker of tumor progression 31 . The total cholines (Cho, PCho and GPCho) level detected by 1 H MRS in vivo was shown to be associated with the endometrial tumor grade 34 , whereas the elevations of PCho in the blood 35 and in the cervicovaginal fluid 36 were reported at an early stage of tumor development. We found the elevated total choline containing compounds in the tumoral tissue as compared to the healthy endometrium, albeit with no association to tumor malignancy (not shown).…”
Section: Discussionmentioning
confidence: 95%
“…The menopausal status was found to be associated with higher dietary requirement for choline 40 . Interestingly, the choline levels in endometrial tumors measured with the use of in vivo 1 H MRS are higher in younger patients (age below 66 years) than in older ones 34 . Our preliminary results also indicate that in the post-menopausal women the choline levels are markedly lower while the phosphoethanolamine (involved in sphingomyelin metabolism) levels are higher than in the pre-menopausal ones (the data not shown).…”
Section: Discussionmentioning
confidence: 98%